2015
DOI: 10.1016/j.vph.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial expression analysis of osteopontin and its splice variants in patients affected by end-stage idiopathic or ischemic dilated cardiomyopathy

Abstract: Osteopontin (OPN) is a phosphoglycoprotein of cardiac extracellular matrix and it is still poorly defined whether its expression changes in failing heart of different origin. The fulllength OPN-a and its isoforms (OPN-b, OPN-c) transcriptomic profile were evaluated in myocardium of patients with dilated or ischemic cardiomyopathy (DCM n = 8; LVEF% = 17.5±3; ICM n = 8; LVEF% = 19.5±5.2) and in auricle of valvular patients (VLP n = 5; LVEF %50), by Real-time PCR analysis. OPN-a and thrombin mRNA levels resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…It is also strongly associated with future ischemic stroke in patients with AF during anticoagulant treatment 34 . Recently, it was shown that humans express multiple OPN isoforms that have different functional effects 35 . However, the importance of these isoforms in vascular pathophysiology, CVD, and AF is still elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also strongly associated with future ischemic stroke in patients with AF during anticoagulant treatment 34 . Recently, it was shown that humans express multiple OPN isoforms that have different functional effects 35 . However, the importance of these isoforms in vascular pathophysiology, CVD, and AF is still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…34 Recently, it was shown that humans express multiple OPN isoforms that have different functional effects. 35 However, the importance of these isoforms in vascular pathophysiology, CVD, and AF is still elusive.…”
Section: Ta B L E 2 Baseline Characteristics and Concentrations Of Es...mentioning
confidence: 99%
“…There is evidence regarding that the sRANKL/OPG complex may relate to HFrEF development, whereas circulating levels of OPN and OPG corresponded to HFpEF (Berezin and Kremzer, 2014a, c). Moreover, an expression of OPN, OPG and OSN genes in myocardium or vasculature sufficiently distinguished in HFrEF and HFpEF and thereby it has been suggested that BRPs could be markers to suggest the development of different HF phenotypes (Cabiati et al, 2016). Indeed, in the PEACE trial levels of OPN were independently associated with the composite CV outcomes and incident HFpEF hospitalization (Abdalrhim et al, 2016).…”
Section: Bone-related Proteinsmentioning
confidence: 99%